Using Behavioral Engagement Measures of Multiple Learning Profiles to Recognize Twice-Exceptional Students. Issue 1 (January 2023) - Hulsey, Donna B.; Moten, Titus R.; Hebda, Maryann R.; Sulak, Tracey N.; Bagby, Janet H.
Using the ECLS-K:2011, a nationally representative dataset, we compared measures of behavioral engagement among students with four different learning profiles: students identified with learning disabilities, students identified as gifted, students identified as both gifted and having a learning disability (twice-exceptional; 2e), and general education students. Behavioral engagement focuses on conduct in class, participation in school-related activities, and interest in academic tasks. We detected differences in engagement among the four learner profiles, specifically when comparing students with disabilities to other profiles. When comparing students with disabilities and general education students to gifted and 2e students, the effect size was medium to large. The effect size between the gifted and 2e profiles was small, suggesting similar behavioral engagement. Because disabilities and giftedness can often "mask" each other, these findings suggest that recognizing how behavioral engagement manifests in each category can lead to more accurate identification of special-needs students for GT assessment.